Evaluation of bacteriophage therapy of Aeromonas hydrophila infection in a freshwater fish, Pangasius buchanani - Kumari, Ritu; Yadav, Ragini; Kumar, Deepak; Chaube, Radha; Nath, Gopal (Frontiers in Aquaculture, 2023)
Introduction The present study aimed to optimize the doses and schedule of specific bacteriophage cocktails in freshwater fish infections as prophylactic and therapeutic measures. Methods The three most active phages against Aeromonas hydrophila (A. hydrophila) (φAHBHU12, φAHBHU16, and φAHBHU19) were characterized phenotypically and genotypically. Intramuscular and water immersion routes were used to calculate the absolute lethal dose of A. hydrophila in Pangasius buchanani. Phage therapy was given simultaneously and after 6, 12, and 24 h of bacterial challenge through intramuscular and water immersion routes. Results The prophylactic and early phage administration could save the fish. Furthermore, the dose of intramuscular 1.0 × 104 plaque-forming unit (PFU)/fish and water immersion 1.0 × 106 PFU mL–1 of the phage cocktail was optimal. Discussion The efficacy of bacteriophage therapy as preventive or curative measures practical when administered simultaneously or early hours of A. hydrophila infection in aquaculture systems. Phage-based approaches may be used as an alternative to antibiotics in aquaculture to reduce antibiotic use as a part of the “One Health” approach.